Performance of fimiculous dung beetles (Coleoptera: Scarabaeidae sensu stricto) in areas of cattle: benefic potencial for the city of Bagé, Rio Grande do Sul State, Brazil (Revista de Ciências Agroveterinárias, 2007)
The Campaign region of Rio Grande do Sul State, and especially the city of Bagé, has great areas destined to the cattle-raising. In this context, the dung beetles (Coleoptera: Scarabaeidae sensu stricto) are important basic components for the maintenance of these ecological systems. These beetles help to biologically control the fly Haematobia irritans (Linnaeus, 1758) (Diptera: Muscidae) and to incorporate bovine dungs in the ground, improving the soil physical and chemical properties. Some studies had already proven the beneficial performance of these beetles in Brazil. However, no work was carried in the Campaign region of Rio Grande do Sul, nor in the city of Bagé. This literature review aims to describe and explain the potentialities of the coprophagous individuals of the Scarabaeidae family to act on dung masses of bovines in cattle areas of the city of Bagé, Rio Grande do Sul. The Scarabaeidae family beetles performance in areas destined to cattle production is extremely beneficial for the balance of ecosystems. Currently, information gathered in different regions showed that these insects are successfully used to control the one fly-of the-horns and nematodes parasites, and to incorporate dung masses in the ground, opening bases so that similar studies are performed in the city of Bagé and through the region of Campaign of Rio Grande do Sul. Such studies have to establish strategies or techniques to design a more ecological cattle production system that does not harm the scarab insects present in natural fields and pastures of the region.
Keywords: Scarabaeidae; Coleoptera; ecologic importance; cattle-raising; Bagé.